Komunikasi Organisasi Kelompok Wanita Tani Pesona Asri: (Studi Kasus: Dalam Program Kwt Desa Klumprit, Kecamatan Mojolaban, Kabupaten Sukoharjo) - Putri Ismaya, Silvia; Hindra Hastuti, Nurnawati; Sihabuddin, Sihabuddin (Solidaritas, 2024)
The government's empowerment program through the Women's Farmers Group (KWT)aims to improve the economy, food security and empower women. However, KWT PesonaAsri in Klumprit Village faced communication barriers that affected the effectiveness ofthe program. This research aims to identify these barriers, in order to become a referencefor other areas with similar problems. This research uses a qualitative descriptive methodto understand the communication barriers of KWT Pesona Asri members in preventingstunting in Klumprit Village. Through interviews, observation and documentation,researchers collected data from KWT members, who are women farmers. This KWT hasunique potential and superior products that are beneficial to society. Data validity wasobtained by triangulating sources and methods. This research uses in-depth interviews,observation and documentation to analyze communication barriers at KWT Pesona Asri,Klumprit Village. The results showed that communication barriers included members'low initiative, misunderstandings, and members' busyness, which affected programeffectiveness. Improvement efforts include evaluation and emotional approaches toincrease communication and participation. Research shows that communication at KWTPesona Asri faces human, technical and situational obstacles. These obstacles includemiscommunication, lack of member dexterity, and lack of active participation, as well asphysical obstacles such as drought. Ineffective communication hinders goal achievement,reduces productivity, and affects harvest yields and catfish cultivation.Keywords: Communication barriers, Farming Women's Group.